Undermined market discipline: The role of bank rescues and bailout expectations - Florian Hett; Johannes Kasinger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Effective market discipline incentivizes financial institutions to limit their risk-taking behavior, making it a key element for financial regulation. However, without adequate incentives to monitor and control the risk-taking behavior of financial institutions market discipline erodes. As a consequence, bailing out financial institutions, as happened unprecedentedly during the recent financial crisis, may impose indirect costs to financial stability if bailout expectations of investors change. Analyzing US data covering the period between 2004 and 2014, Hett und Schmidt (2017) find that market participants adjusted their bailout expectations in response to government interventions, undermining market discipline mechanisms. Given these findings, policymakers need to take into account the potential effects on market discipline when deciding about public support to troubled financial institutions in the future. Considering the parallelism of events and public responses during the financial crisis as well as the recent developments of Italian banks, these results not only concern the US, but also have important implications for European financial markets and policy makers.
urn:nbn:de:hebis:30:3-438834
Keywords: 330; bailout; market discipline; financial institutions; financial crisis; banks